Coumarin Content and Anti-Bilharzial Activity of Extracts of Leaves of Citrusaurantifolia (Lime) and Citrus Limonia (Lemon) - G. Haggag, Eman; Abdel Wahab, S.M.; El-Zalabany, S.M.; Abou Moustafa, E.A.; El-Kherasy, E.M.; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
Coumarins were isolated and identified from the leaves ofCitrus aurantifolia and C. limonia; the percentage yields were 3.1and 2.7%, respectively. Bergapten, limettin, isopimpinellin andumbelliferone were obtained from both species; however, this is thefirst report of the four compounds from lemon leaves. Xanthotoxin,found only in lime leaves is reported here for the first time fromthe genus Citrus. The anti-bilhanial activity of the crude coumarinconcentrates from the alcohol extracts of both species was foundto be just slightly less than pure isopimpinellin, a coumarin withknown high activity.